Furtherance of Multilevel Inverter and Evolution of a Packed Inverter Unit for Dynamic Loads - Premkumar R; Vimal Juliet A; Vijayaraja L (Elektronika ir Elektrotechnika)
Multilevel inverters (MLIs) provide a solution for high-power applications due to the production of a high-quality output voltage with low harmonic distortion. This technology is gaining popularity in the power industry for applications such as renewable energy systems, motor drives, and electric vehicles. MLIs are categorised on the basis of the number of levels in their output waveform. This article includes a discussion of two, three, and higher-level inverters with respect to design aspects and their application in the power industry, contributing to the development of sustainable and efficient systems. In addition, a packed inverter unit (PIU) with 11 IGBT switches and three uneven DC voltages is used to generate 11 voltage steps. From the suggested axioms, the amplitude of the DC sources is chosen to generate larger voltage steps with the fewest possible circuit components. Additionally, an 11-level inverter is simulated for fixed and variable R/RL loads. A comparison analysis of the circuit components between the developed circuit and existing MLIs is carried out. Finally, 11-level inverters are evaluated in real time for constant, fluctuating R/RL loads, and various performance metrics are noticed.